Effect of Tongxinluo on pulmonary hypertension and pulmonary vascular remodeling in rats exposed to a low pressure hypoxic environment. (24th December 2016) - Wang, Yong; Ma, Ting-Ting; Gao, Na-Na; Zhou, Xiao-Ling; Jiang, Hong; Guo, Rui; Jia, Li-Na; Chang, Hong; Gao, Ying; Gao, Zhi-Min; Pan, Lei
Abstract: Ethnopharmacological relevance: Tongxinluo (TXL), which is a Chinese medicine rooted from traditional used herbs, has been used in clinic to treat cardiovascular and cerebrovascular diseases. However, it remains unknown whether TXL alleviates low pressure hypoxic pulmonary hypertension. Aim of the study: Here, we aimed to observe the influence of TXL on pulmonary hypertension in a rat model that exposed to high altitude environment characterized by low pressure hypoxia. Materials and methods: A total of 32 male Sprague-Dawley rats were divided into four groups: control group (normal pressure and normoxia), pulmonary hypertension group (PAH, the parameter is equal to that in altitude 5000 m), TXL group (rats living in environment equal to that at altitude of 5000 m received TXL treatment), vardenafil group (VDNF, rats living in environment equal to that altitude of 5000 m received vardenafil treatment). The high altitude environment was created in chamber by adjusting the inner pressure and oxygen content concomitantly. Before entering the chamber, the TXL group was given TXL (1.2 g kg −1 d −1 ) for 28 days, and the VDNF group was given VDNF (0.1 g kg −1 d −1 ) for 28 days. After 28 days, the mean pulmonary artery pressure (mPAP) and right ventricular pressure was measured using right heart catheterization. The weight of the right ventricle (RV), left ventricle (LV) and interventricular septum (IVS) was measured, and the right ventricular mass index was calculated. Lung tissue was subjected to hematoxylin and elastic fiber staining, and the medial wall thickness (MT), medial wall cross-sectional area (MA), MT%, and MA% were measured. Proliferative activity within the pulmonary arteries was quantified by Ki67staining. Results: After 28 days, as compared with that in normal control group, animals living in the chamber (PAH group) showed a significant increase in mPAP( 47.5 mmHg versus 18 mmHg), RV/LV+IVS (0.45 versus 0.21) and MA% (78% versus 44%), respectively. Administration of TXL resulted in a significant decrease of 20 mmHg in mPAP, returning of RV/LV+IVS to 0.27, and a 40% reduction in MT% compared with that in PAH group. In the VDNF group, RV/LV+IVS and MT% was 0.268 and 38.77, significantly lower than that in PAH group. While, mPAP increased by 12.5 mmHg with treatment by VDNF. In contrast to the PAH group, alpha- Smooth Muscle Actin (α-SMA reduced by 19% in the TXL group (p=0.005) and 16% in the VDNF group (p=0.01). Ki67 expression in the VDNF group was significantly lower than the PAH group (P<0.01). Ki67 expression in the TXL group was significantly lower than the PAH group (P<0.01). Compared with the VDNF group, the indexes above reduced in the TXL group. Our results indicate that TXL significantly reduces pulmonary artery pressure, right ventricular hypertrophy, pulmonary small artery wall thickness, and luminal stenosis. In addition, smooth muscle proliferation markedly decreased and muscular artery decreased. However, TXL was unable to restore parameters to control levels. Conclusions: The automatic-adjusted low pressure hypoxic chamber was capable of establishing a pulmonary hypertension rat model at an altitude of 5000 m. Compared with VDNF, TXL decreased mPAP and right ventricular hypertrophy index (RVHI) in the pulmonary hypertension rat model, and prevented vascular remodeling by reducing small pulmonary artery thickening, smooth muscle thickening and proliferation. Thus, TXL may be a potential treatment for pulmonary hypertension. Graphical abstract: